“The Commission” La comunicazione su due binari paralleli - Gallerani, Enrico; Belluto, Martina (Comparative Cultural Studies: European and Latin American Perspectives, 2019)
This paper explores the gaps in communication, which may take place during the administrative procedure to asylum seekers in order to evaluate their request for protection under international law. Starting from ethnographic research carried out at refugee centres in the province of Ferrara (Italy), the analysis will focus on the normative linguistic register used, according to national and international guidelines, by the Territorial Commissions. Comparing them with the process of interviewing, and other case-studies, this research stresses some recurring narratives and possible asymmetries that could arise during the conversation between the Commission and asylum seekers with their life histories. As emerged here, the complexity and the limits of this communicative interaction, especially during the interviews, is not limited to the moment of examination, but lead to broader forms of social discrimination.